Isolation and Characterization of DkPK Genes Associated with Natural Deastringency in C-PCNA Persimmon - Guan, Changfei; Chen, Wenxing; Mo, Rongli; Du, Xiaoyun; Zhang, Qinglin; Luo, Zhengrong (Frontiers in Plant Science, 2016)
Chinese pollination-constant nonastringent (C-PCNA) persimmon (Diospyros kaki Thunb.) is considered to be an important germplasm resource for the breeding of PCNA cultivars, though its molecular mechanisms of astringency removal remain to be elucidated. Previously, we showed that the abundance of pyruvate kinase gene (PK) transcripts increased rapidly during astringency removal in C-PCNA persimmon fruit. Here, we report the full-length coding sequences (CDS) of six novel DkPK genes from C-PCNA persimmon fruit isolated based on a complementary DNA (cDNA) library and transcriptome data. The expression patterns of these six DkPK genes and correlations with the soluble proanthocyanidin (PA) content were analyzed during various fruit development stages in different types of persimmon, with DkPK1 showing an expression pattern during the last stage in C-PCNA persimmon that was positively correlated with a decrease in soluble PAs. Phylogenetic analysis revealed that DkPK1 belongs to cytosolic-1 subgroup, and subcellular localization analysis confirmed that DkPK1 is located in the cytosol. Notably, tissue expression profiling revealed ubiquitous DkPK1 expression in different persimmon organs, with the highest expression in seeds. Furthermore, transient over-expression of DkPK1 in persimmon leaves resulted in a significant decrease in the content of soluble PAs but a significant increase in the transcript levels of pyruvate decarboxylase genes (DkPDC1, -3, -4, -5), which catalyze the conversion of pyruvate to acetaldehyde. Thus, we propose that an acetaldehyde-based coagulation effect reduces the content of soluble PAs. Taken together, our results suggest that DkPK1 might be involved in the natural removal of astringency at the last developmental stage in C-PCNA persimmon. This is the first report to identify several novel full-length DkPK genes as well as their potential roles in the natural loss of astringency in C-PCNA persimmon.